Issues in the implementation of Sijil Tinggi Agama Malaysia - Roslan, Samsilah; Suhid, Asmawati; Mahyuddin, Rahil; Mohamad, Muhd Fauzi; Abdul Mutalib, Lukman (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The Sijil Tinggi Agama Malaysia (STAM) programme was introduced in 2000 with the purpose of producing quality pre-university students in Malaysia who have equivalent qualifications with graduates from the matriculation center of EI-Azhar University in Egypt or Ma'ahad Bu'uth Islamiyyah AI-Azhar As-Syarif. In order to achieve this objective, the curriculum and text book used for the STAM programme are the same with the matriculation center in Egypt. This programme is conducted in selected religious secondary schools throughout Malaysia for Form Six students. Although it has been implemented for several years, there has never been any structured effort to really look into the issues faced by those directly involved with the programme, namely the schools, the teachers and students themselves. This study was conducted in five randomly chosen schools to identify the issues and challenges faced and explore the means and ways to improve the programme. A questionnaire and semi-structured interviews generated both quantitative and qualitative findings. The study showed that there are issues related to the shortage of text and reference books and expert teachers to conducts the programmes, the language as well as the syllabus for multiple courses. All respondents express concerns related to the amount of multiple subjects that the students are required to master with no allocation for streaming into specific categories such as Usuluddin or Syariah. The suggestions from all the respondents were tabulated in specific categories and summarized for relevant parties to take action.